One Direction? A Tutorial for Circular Data Analysis Using R With Examples in Cognitive Psychology - Cremers, Jolien; Klugkist, Irene (Frontiers in Psychology, 2018)
Circular data is data that is measured on a circle in degrees or radians. It is fundamentally different from linear data due to its periodic nature (0º = 360º). Circular data arises in a large variety of research fields. Among others in ecology, the medical sciences, personality measurement, educational science, sociology and political science circular data is collected. The most direct examples of circular data within the social sciences arise in cognitive and experimental psychology. However, despite numerous examples of circular data being collected in different areas of cognitive and experimental psychology, the knowledge of this type of data is not well-spread and literature in which these types of data are analysed using methods for circular data is relatively scarce. This paper therefore aims to give a tutorial in working with and analysing circular data to researchers in cognitive psychology and the social sciences in general. It will do so by focusing on data inspection, model fit, estimation and hypothesis testing for two specific models for circular data using packages from the statistical programming language R.